Possibilities and limitations of economically valuating ecological damages - Stefan Bayer (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
Ecological damages have to be evaluated in monetary terms for implementation in an economic analysis. Economic theory is based upon individual preferences (methodological individualism): Ecological damages can only be socially evaluated when individual values are available. However, in sharp contrast to marketable goods and services, ecological damages generally are pure public goods and, thus, market prices as a lower value bound do not exist. Therefore, we have to use alternative evaluation methods to get economic values of ecological damages. In this paper, we concentrate on four main points of the evaluation of ecological damages in economic models: Firstly, we show the general economic approach to obtain values of nonmarketable goods and services on a micro economic level. Afterwards, we discuss the assumptions and shortcomings of the economic approach. Thirdly, we determine optimal social environmental levels from a macroperspective which is followed by an analysis of the applicability of this approach. Some summarizing remarks close the paper.
urn:nbn:de:bsz:21-opus-18823
Keywords: 330; Umweltbelastung; Bewertung; Präferenztheorie; Kosten-Nutzen-Analyse; Soziale Kosten; Theorie